2019
DOI: 10.1186/s12906-019-2436-5
|View full text |Cite
|
Sign up to set email alerts
|

Critical pharmacokinetic and pharmacodynamic drug-herb interactions in rats between warfarin and pomegranate peel or guava leaves extracts

Abstract: BackgroundIn-depth information of potential drug-herb interactions between warfarin and herbal compounds with suspected anticoagulant blood thinning effects is needed to raise caution of concomitant administration. The current study aimed to investigate the impact of co-administration of pomegranate peel and guava leaves extracts, including their quality markers namely; ellagic acid and quercetin, respectively, on warfarin’s in vivo dynamic activity and pharmacokinetic actions, in addition to potential in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
0
14
0
8
Order By: Relevance
“…For example, data show that ellagic acid from pomegranate peel guava leaf extract can significantly increase the AUC of warfarin with concomitant use. A significant reduction in CYP2C8, 2C9, and 3A4 activity was the main reason for this interaction 23 .…”
Section: Determinants Of Pkmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, data show that ellagic acid from pomegranate peel guava leaf extract can significantly increase the AUC of warfarin with concomitant use. A significant reduction in CYP2C8, 2C9, and 3A4 activity was the main reason for this interaction 23 .…”
Section: Determinants Of Pkmentioning
confidence: 89%
“…UGT1A4 is involved in the glucuronidation of metizolam 42 . Other UGT isoforms involved endogenous and exogenous substrates are listed in Table 2 23 , 43, 44, 45, 46.…”
Section: Determinants Of Pkmentioning
confidence: 99%
“…However, people are becoming increasingly aware of the importance of DDIs. In the last few years, several studies on the interactions between flavonoids and drugs have been reported (Seden et al 2010;Alnaqeeb et al 2019;Zhao et al 2019). Given the potential antiinflammatory effects of naringenin, it is often used together with tofacitinib for the treatment of rheumatoid arthritis in Chinese clinics Ananth et al 2016;Banerjee et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Surya Sandeep et al (2014) reported that naringenin significantly increases the bioavailability of orally administered felodipine, a P-glycoprotein and CYP3A4 substrate drug, in rats, through the inhibition of intestinal P-gp and CYP3A4 [13]. Alnaqeeb et al (2019) reported that quercetin and guava leaf extracts in combination with warfarin exert a greater increase on warfarin's C max and International Normalized Ratio values than when used alone, indicating the inhibition of CYP2C8, 2C9 and 3A4, major warfarin-metabolizing enzymes [14]. Biflavonoids, formed by the covalent bond between two monoflavonoids, are a subclass of flavonoid [15].…”
Section: Introductionmentioning
confidence: 99%